Pharmacognosy phytochemistry medicinal plants - Bruneton, Jean; Hatton, Caroline K. (Hampshire Intercept, 1999)
This new edition of Jean Bruneton's book has been revised and expanded with over 200 additional pages reflecting the most recent advances in natural and semisynthetic substances. It also features the most recent additions to the therapeutic arsenal such as antimalarial, antitumor, and antiretroviral agents. Drawing on biosynthetic relationships, the book describes both the primary and secondary classes of metabolites and the drugs from which they originate. Phytochemical generalities, distribution, biosynthesis, extraction and quantitation methods, and biological aspects are developed for each class. All raw materials are meticulously detailed giving origin, identity, production, composition, uses, processing and optimization. The result is a considerable amount of botanical, chemical, analytical, pharmacological, and therapeutic data gathered into this truly comprehensive compilation. Therapeutic indications and recommended usage are specified for each product. An extensive index with almost 3000 entries and some 500 references are a valuable starting point for a search of the literature. This "encyclopedia" of pharmacognosy and phytochemistry is written for students, teachers, and professionals who use plant resources in pharmacy, cosmeticology, perfumery, botany, food technology and related fields.
Keywords: PHARMACOGNOSY; PHARMACOGNOSY